Perspectives for the Constitution of a Culture of Participation in Social Issues in Science and Technology - Rosa, Suiane Ewerling da (2021)
Among other objectives, the science-technology-society movement (STS) in science education aims at the democratization of decisions involving social issues related to science and technology. Bearing in mind that such purpose can be understood in different ways, we defend an expanded perspective of social participation. Thus, the following research focuses on defining and characterizing elements that contribute to situate and constitute expanded mechanisms for participation in social themes that involve science-technology. Therefore, we carried out an investigation of theoretical and practical nature, based on references from different fields of study, including Science Education. As a result, it seems that this perspective of participation in terms of cultural action is motivated by transformative purposes, from which we highlight three constitutive elements: value, knowledge, and social engagement. Subsequently, we present theoretical-practical problematizations and foundations regarding these elements, understanding that they can help chart paths towards the constitution of broader democratic processes in the context of the STS movement in Science Education.